Doença pulmonar obstrutiva crônica (DPOC) e ansiedade : adaptação do copd anxiety questionnaire-revised (CAF-R) - Cunha, Rafaela Cassol da (2021)
Chronic Obstructive Pulmonary Disease (COPD) is recognized as an important public health problem and is evaluated as being the third leading cause of death in the world in 2019. Psychiatric comorbidities, such as anxiety, have been associated with clinical complications, higher frequency in hospital admissions and worse prognosis. The Theoretical Section of this dissertation aimed to deepen the discussion on the relationship between anxiety and COPD, through a brief literature review. The variability found in the data on the prevalence of anxiety in this population, as well as in the associations between anxiety and disease severity, points to barriers in the measurement of the construct, which may be explained by the use of non-specific instruments for this clinical condition. The Theoretical Section pointed to limitations regarding the measurement of anxiety in this population, since broader instruments are often not sensitive in the correct identification of anxious conditions and in the association regarding the severity of the disease. The Empirical Section aims to adapt and investigate the first evidence of validity of the COPD Anxiety Questionnaire – revised (CAF-R) for the Brazilian context. The study included 127 participants diagnosed with COPD, who answered a questionnaire with sociodemographic and clinical questions and instruments for assessing anxiety: The Hospital Anxiety and Depression Scale (HADS) and COPD Anxiety Questionnaire – revised. The results presented in the Empirical Section demonstrated that CAF-R is a valid instrument with good reliability indexes. Through Confirmatory Factor Analysis, the theoretical model of five factors demonstrated a better fit, maintaining the internal structure of the instrument. The correlations conducted between HADS, CAF-R and disease severity demonstrated a greater capacity of CAF-R in the identification of the COPD severity levels, as well as a better understanding of the specific fears that seem to accompany patients diagnosed with COPD. The evaluation of anxiety through a more focused instrument related to the disease process may contribute to more assertive prevalence data, as well as to more effective referrals and interventions. Future studies that may seek new evidence of instrument validity through enlarged samples and using the original response scale (Likert type of 5 points) are suggested. Correlations with the presence of other comorbidities, both clinical and psychiatric, may also contribute to the investigation of the validity of the instrument. In addition, longitudinal studies are important for the monitoring of anxiety along with the progression of COPD and for predicting possible reduction of patient functionality.